2023
DOI: 10.1101/2023.09.01.23294897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Definitions of digital biomarkers: a systematic mapping of the biomedical literature

Ana Karen Macias Alonso,
Julian Hirt,
Tim Woelfle
et al.

Abstract: Background Technological devices such as smartphones, wearables, sensors, or virtual assistants allow to collect data on health and disease processes and are thus increasingly considered a useful digital alternative to conventional biomarkers. We aimed to provide a systematic overview of the emerging literature on "digital biomarkers" with their definitions, features, and citations in biomedical research. Methods We analyzed all articles in PubMed that used the term "digital biomarker(s)" in title or abstract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Babrak (2019) discusses the basic differences and similarities between traditional and digital biomarkers and points out the necessity for synchronization and unique feature definition claiming, therefore, that the unclear definition of digital biomarkers, population groups, and their intersection with traditional biomarkers hinders their discovery and validation [ 22 ]. Finally, and recently, Alonso et al (2023) even concluded that there is no consensus about what this emerging term means [ 75 ].…”
Section: Digital Tools Allow Cognitive Decline Detectionmentioning
confidence: 99%
“…Similarly, Babrak (2019) discusses the basic differences and similarities between traditional and digital biomarkers and points out the necessity for synchronization and unique feature definition claiming, therefore, that the unclear definition of digital biomarkers, population groups, and their intersection with traditional biomarkers hinders their discovery and validation [ 22 ]. Finally, and recently, Alonso et al (2023) even concluded that there is no consensus about what this emerging term means [ 75 ].…”
Section: Digital Tools Allow Cognitive Decline Detectionmentioning
confidence: 99%